(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The accelerated digital transformation of economic, governmental, and social systems has fundamentally reshaped the global crime landscape, resulting in a marked escalation in cybercrime and digital fraud. Threat actors increasingly exploit emerging technologies such as artificial intelligence (AI), cloud computing, cryptocurrencies, and automation to scale attacks, evade detection, and monetize illicit activities. This study critically appraises emerging trends in cybercrime and digital fraud through an empirical investigation grounded in socio-technical and governance perspectives. Using survey data from 312 cybersecurity professionals across three regions and triangulating the findings with authoritative global cybercrime reports, the study examines the relationships among technological enablers, organizational vulnerabilities, regulatory governance, and cybercrime impact outcomes. Reliability testing, correlation analysis, and multivariate regression modeling provide evidence that AI-enabled fraud, ransomware-as-a-service, identity-centric attacks, and cryptocurrency-related crimes significantly increase financial losses, operational disruption, and reputational damage. Regulatory governance is found to moderate, though not eliminate, these impacts. The study contributes empirical validation to cybercrime scholarship, advances an integrated conceptual framework, and offers evidence-based recommendations for policymakers, regulators, and organizational risk managers.